2022
DOI: 10.21203/rs.3.rs-2201972/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atomic-level Chemical Reaction Promoting External Quantum Efficiency of Organic Photodetector Exceeding 10^8% for Weak-Light Detection

Abstract: Low-cost, solution-processed photomultiplication organic photodetectors (PM-OPDs) with external quantum efficiency (EQE) above unity have attracted enormous attention. However, their weak-light detection is unpleasant because the anode Ohmic contact causes exacerbation in dark current. Here, we introduce atomic-level chemical reaction in PM-OPDs which can simultaneously suppress dark current and increase EQE via depositing a 0.8 nm thick Al2O3 by atomic layer deposition. Suppression in dark current mainly orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…[28][29][30] These devices incorporate minimal acceptor content in organic BHJ layers, acting as electron traps to enhance hole injection, known as the charge injection narrowing (CIN) effect. [31][32][33] For instance, Wang et al reported red-light PM-OPDs with an EQE of 53 500% using a 2.5 mm thick P3HT:PC 71 BM layer at a high À60 V bias. 34 Similarly, NIR PM-OPDs incorporating PTB7-Th achieved EQEs around 2000% at À50 V. 35 Suthar et al proposed a narrowband PM-OPD at low external biases through a pseudo bilayer structure comprising a photon-filtering layer and a PM layer.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] These devices incorporate minimal acceptor content in organic BHJ layers, acting as electron traps to enhance hole injection, known as the charge injection narrowing (CIN) effect. [31][32][33] For instance, Wang et al reported red-light PM-OPDs with an EQE of 53 500% using a 2.5 mm thick P3HT:PC 71 BM layer at a high À60 V bias. 34 Similarly, NIR PM-OPDs incorporating PTB7-Th achieved EQEs around 2000% at À50 V. 35 Suthar et al proposed a narrowband PM-OPD at low external biases through a pseudo bilayer structure comprising a photon-filtering layer and a PM layer.…”
Section: Introductionmentioning
confidence: 99%